PROFIL KLINIS DAN NEUROIMAGING PASIEN CAROTID CAVERNOUS FISTULA DI RUMAH SAKIT WAHIDIN SUDIROHUSODO MAKASSAR - Ardhany, Andri; GOYSAL, YUDY (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Introduction: Carotid cavernous fistula (CCF) is a rare abnormal connection between the carotid artery and the cavernous sinus. Based on its etiology, CCF is divided into traumatic and spontaneous types. CCF presents with varied clinical findings and neuroimaging features. Diagnosis is established based on clinical findings and neuroimaging characteristics. Objective: This study aims to provide a descriptive overview of clinical profile and neuroimaging of CCF patients at Wahidin Sudirohusodo Hospital, Makassar. Method: This descriptive study retrospectively collected data from medical records of Wahidin Sudirohusodo Hospital, Makassar, from January 2023 to March 2024, using total sampling method. Results: A total of 25 subjects meeting the criteria were obtained. The mean age was 33.08Ã‚Â±15.37 years, predominantly male (76%). The duration of symptoms was mostly >1 month (88%). Trauma was the most common etiology (76%). Unilateral lateralization was most frequent (84%). The most common symptoms and signs were proptosis (80%), conjunctival injection (60%), and headache (52%). Cranial nerve VI involvement was most frequent (52%). All subjects had direct CCF anatomical characteristics. Imaging features included dilated superior ophthalmic vein (92%), proptosis (76%), and cavernous sinus enlargement (36%). Discussion: Traumatic etiology was more common than spontaneous in CCF, consistent with other studies finding traumatic etiology most prevalent in direct CCF patients. Symptoms and signs such as proptosis, conjunctival injection, headache, and imaging features like dilated superior ophthalmic vein, proptosis, and cavernous sinus enlargement on CT scan or MRI suggest CCF. Keywords: Carotid-Cavernous Fistula, Proptosis, Cavernous Sinus